Praktik Kepemimpinan Berbasis Nilai (Value-Based Leadership) di SMP Negeri 1 Lembang dan SMP Darul Hikam Internasional - Maria Vatmawaty Bety; Nurdin Nurdin; Asep Sopian; Dinar Samsunizar (Jurnal Intelek Insan Cendikia, 2025)
Value-based leadership is effective school principal leadership that can bring about positive moral changes for teachers, staff, and students. Similarly, the leadership practices implemented by school principals at SMP Negeri 1 Lembang and SMP Darul Hikam Internasional, both A-accredited excellent schools, with the application of moral values-based education thru school programs and habituation activities. This study aims to determine the practice of value-based leadership in both schools, as well as the challenges and obstacles faced by the two school principals and their implications for the field of education. The research method is descriptive qualitative, processing data from data collection techniques such as observation, document study, questionnaire distribution, and open interviews with school principals and teacher representatives. The research results indicate that the leadership practices at SMP Negeri 1 Lembang and SMP Darul Hikam International are: moral values orientation as the foundation of leadership, character formation process as participatory leadership practice, communication and example as the core of value-based leadership, ethical decision-making and handling moral dilemmas, transparency, integrity, and a culture of mutual respect, consistency, and value-based innovation. And the practical and policy implications of values-based leadership for its implementation in schools.